Evidências pré-clínicas da ação antinociceptiva do 3-fenil-5-(4-etilfenil)-imidazolidina-2,4-diona em estudos psicofarmacológicos - Queiroz, Ronaldo Bezerra de (2011)
Imidazolidine derivatives are synthetic products with many different therapeutic applications. Many imidazolidine derivatives have pharmacological properties at the level of the CNS, such as phenytoin, which is used in clinical practice as an anticonvulsant. However, this also works effectively in the treatment of neuropathic pain and it has been already used as anti-arrhythmic heart. The 3-phenyl-5-(4- ethyphenyl)-imidazolidine-2,4-dione (IM-3), recently synthesized from amino acid was selected for psychopharmacological studies. Based on the chemical and structural similarity, this study investigated the antinociceptive activity of IM-3 in animal models. The study has began with screening and behavioral pharmacology of the LD50 determination. In the screening results indicate a depressant activity on CNS and from the LD50 doses were chosen for subsequent tests with 50, 100 and 200 mg / kg intraperitoneally. In the next step, methodologies to evaluate the specific antinociceptive activity were used. The first was the writhing induced by acetic acid; afterwards, the formalin test and finally the hot plate test, which is specific for the central antinociceptive activity. In the three methodologies used, the IM-3 showed to be effective in the writhing test by acetic acid at a dose of 200 mg/kg which increased both the latency to the onset of writhing and reduced the number of writhing in the control group and in the formalin test at doses of 100 and 200 mg / kg decreased the time of the paw lick in the second phase of testing. Therefore, from these experimental data, it is possible to infer that the IM-3 has antinociceptive activity of the anti-inflammatory type.